Penerapan Pembelajaran Matematika Berbasis Kearifan Lokal Gerabah dengan Model PjBL terhadap Hasil Belajar Siswa - Amalia, Nafiatul; Riswari, Lovika Ardana; Pratiwi, Ika Ari (Universitas Muria Kudus, 2024)
Monotonous and conventional learning processes with teacher-focused learning methods and a lack of understanding of local regional culture cause low student learning outcomes. The aim of this research is to calculate the increase in student learning outcomes by utilizing local wisdom in mathematics learning using the PjBL model. Pottery wisdom is a cultural characteristic that is passed down from generation to generation in society. PjBL is a learning model that consists of learning units that are process-centered and relatively long-term. This research uses a quantitative type 1 group pretest-posttest design method. This research will be conducted on class V students of SDN 3 Dorang. Data collection techniques include interview techniques, observation, documentation and tests. Descriptive statistical data analysis techniques use a prerequisite test, namely the normality test. After the data is normal, it is continued with hypothesis testing using the paired sample t-test. Application of mathematics learning based on local pottery wisdom using the Project Based Learning model on student learning outcomes using the paired sample t-test. Based on this research, it can be concluded that mathematics learning based on local pottery wisdom using the PjBL model can improve student learning outcomes